(untitled) (Research, Society and Development, 2020)
Soybean seeds with IPRO technology have resistance to the herbicide glyphosate and the main caterpillars of the crop, and have stood out in the soybean production chain, occupying increasingly larger planting areas in Brazil and worldwide. Due to the existence of few studies related to post-harvest soybean seeds with IPRO technology, this research aimed to evaluate whether the storage time (360 days, with evaluations every 90 days) and the storage conditions (with control: 12 °C ± 2 and 70% ± 5 RH, and without environmental control) affect the physical, chemical and physiological properties of soybean seeds of cultivar NS 7780 IPRO. A completely randomized design was used, with a 2 x 5 factorial scheme. The storage time and condition caused changes in most of the physicochemical characteristics and in all the physiological properties evaluated of soybean seeds of cultivar NS 7780 IPRO. Storage time negatively influences physiological properties, as well as ash content, pH and luminosity. The condition of uncontrolled storage, in addition to negatively influencing vigor, viability and germination, also influences moisture, water activity and seed color, demonstrating that uncontrolled storage provides faster change of these parameters. The environmental conditions in the region of Goiânia do not preserve the physiological properties of the soybean seed of the cultivar NS 7780 IPRO for a period longer than 90 days. Germination remained adequate until the end of storage with environmental control and the vigor was within the standards established by Brazilian legislation for commercialization only up to 180 days of storage.